PEMANFAATAN TEPUNG DAUN MANGROVE JERUJU (Acanthus ilicifolius) SEBAGAI PENGAWET ALAMI BAKSO AYAM - Jayadi, Faisal; Sukainah, Andi; Rais, Muhammad (Jurnal Pendidikan Teknologi Pertanian, 2018)
This study aims to find out the shelf life of chicken meatball with the addition of flour from mangrove leaves jeruju (Acanthus ilicifolius) as a natural preservative.This research is a quantitative research (experiment) which is done with two process stages. The first process of processing mangrove leaves into flour as a preservative and the second process of making chicken meatball. This study used a complete randomized design (RAL), with concentrations of flour (0%, 5%, 10%, and 15%) and storage at; room temperature, cold temperature, and freezing temperature, with observation parameters; Total Plate Count (TPC), Escherichia coli, Salmonella, and pH. The data obtained will be analyzed by variance analysis and advanced Duncan Multiple Rate (DMRT) test. The results showed that the addition of mangrove leaves jeruju 15% at frozen temperature storage is the best concentration as a chicken meatball preservative